Adolescence and family: The transformation of the Colombian family and its incidence in adolescents (2019)
This book is the result of a research project and aims to show with current data the situation of the Colombian family and its level of responsibility for various problems arising in adolescence. For this purpose, we will present the results of a comparative study in twelve cities of the country with about 1,000 teenagers from three population groups: outstanding students from public and private schools, adolescents using psychoactive substances, and juvenile offenders. Previous research and reflections on the Colombian family and parental relationships, adults as role models for new generations, the different bonds and relationships between parents and children, authority, affectivity, and rules are part of the literature review of this work. The book initially expounds both the conceptual theoretical and methodological frameworks of the research. Then, the results of the study are presented in six chapters, each of which is framed by a discussion with literature relevant to the subject matter. Subsequently, there are two chapters that invite us to reflect on the alternatives necessary to face the transformation of the current Colombian family. Finally, some general conclusions are drawn.Regarding the presence of internalized problems in teenagers, risk factors include poor relationships with parents, presence of a risky context, low levels of psychological well-being, and the death of the father figure at an early age. In contrast, externalized problems are more associated with being male and the relationship with the mother figure, living in a threatening context, having low levels of resilience, and being abandoned by the father at an early age.